IMPLEMENTASI KEBIJAKAN TENTANG PENERIMAAN PESERTA DIDIK BARU DENGAN SISTEM ZONASI SEKOLAH PADA ZONA KEDUA DI SMP NEGERI DENPASAR - Yunita Sriandewi, Ni Luh Putu; Putri Wirantari, I Dewa Ayu; Yudartha, I Putu Dharmanu (CITIZEN CHARTER, 2020)
ABSTRACT Education is currently undergoing a renewal, one of which is by conducting a zoning system during the implementation of New Student Admissions. The purpose of this study was to see how the Implementation of New Student Admission Policy Using the School Zoning System in the Second Zone in Denpasar State Junior High School.Based on research in the field, the implementation of PPDB Policy with the School Zoning System in the Second Zone in Denpasar State Junior High School measured by Van Meter and Van Horn shows that this policy has worked well but not yet maximized due to the finding of several problems that occur in the field such as, websites for PPDB registration with the school zonas system had experienced interference, lack of public understanding related to socialization about the school zoning system, and falsification of family cards Keyword : Implementation, Admission of new students, School zoning